The Politeness Strategies in Directives Speech Acts Found in Daily Conversations among Students - Nana Supriatna; Aneu Sri Gusmayanti; Lanlan Muhria (Jurnal Praktik Baik Pembelajaran Sekolah dan Pesantren, 2023)
This study aims to find out the kinds of Brown and Levinson’s politeness strategy among the senior high school and how they use those strategies in their daily conversations. In this study applied Brown and Levinson’s politeness strategy. This study was a qualitative approach using descriptive method. The subject was the Senior High School Daarul Huda. The source of the data is the students’ spoken expressions which the writer transcribes into conversational texts. The researcher observed the students’ speaking classes, came to their classes before lecturing, and went to their boarding houses. Their conversation were recorded and transcribed. Then, data was analyzed based on Brown and Levinson’s politeness strategy. The result showed there were 166 utterances of Brown and Levinson's politeness strategy that were used by the students in their daily conversations. These  are a bald on-record strategy, a positive politeness strategy, a negative politeness strategy, an off-record strategy and a do not do FTA/ keep the quiet strategy.